A construction manager's technical knowledge competency model for the Malaysian construction industry / Hairuddin Mohammad - Mohammad, Hairuddin (Institute of Graduate Studies, UiTM, 2018)
Malaysian construction industry (MCI) is regarded as one of the significant industry that drives the country forward. Although having recorded 7.4% of positive growth in 2016, the progression of MCI was hampered by a considerable number of recurring problems such as delays, wastages, cost overruns, and disputes. Consequently, contractors' faults are to be blamed, through their incompetent construction manager (CM) to deliver construction projects. Even though there are provisions of education and training for CM, continuous critiques on its ineffectiveness were reported. Eventually, it was observed that lack of term of reference on the technical knowledge competency for CM is became the major setback. Therefore, the research aims to establish generic technical knowledge competency model for CM through three objectives that were outlined by the research, namely; (1) to identify the generic technical knowledge competency of Malaysia's construction managers, (2) to analyse the importance of the generic technical knowledge competency of construction managers towards categories and grades of Malaysia's contractors, and (3) to analyse the corroboration level of the existing CM education and training offered compared to the generic technical knowledge competency. Pragmatic mixed methods research was selected by employing qualitative and quantitative approaches. In short, multi-layered thematic (MLT) analysis was embedded into literature analysis to maintain reliability, before proceeded to validity as in semistructured interviews towards related academicians and practitioners in construction. Later, to analyse, validate and generalise the findings to the masses, questionnaire surveys were distributed to contractors around the peninsular of Malaysia…